Implementasi Nilai Keadilan Sosial dalam Sila Kelima Pancasila sebagai Dasar Pemenuhan Hak Asasi Manusia di Indonesia - Ervianto, Moh Kevin (Maliki Interdisciplinary Journal, 2025)
This study examines the role of social justice values ​​in the fifth principle of Pancasila as the primary foundation for the fulfillment of human rights (HAM) in Indonesia. The background of this study is based on the importance of harmonization between Pancasila and human rights in ensuring equality and the welfare of all citizens, including vulnerable groups and minorities. The research method used is qualitative with a descriptive analytical approach that collects data from literature, policies, and relevant legal decisions. The results of the study indicate that the implementation of social justice values ​​has had a positive impact, such as reducing stunting rates through the Family Hope program, but there are challenges in the form of marginalization of minority groups and obstacles to corruption in policy implementation. The conclusion of the study emphasizes the importance of strengthening education on Pancasila and human rights values, as well as transparent and corruption-free law enforcement to achieve equitable social justice. Recommendations are provided for the government and society to strengthen human rights protection mechanisms and raise awareness of social justice values ​​to maintain a just and inclusive national unity.